New records of entedoninae (Hymenoptera, Eulophidae) for the coffee crop (Coffea arabica L.) - Lara, Rogéria Inês Rosa; Perioto, Nelson Wanderley; Miranda, Natalia Furlan; Fernandes, Daniell Rodrigo Rodrigues; Martinelli, Nilza Maria (Coffee Science - ISSN 1984-3909, 2011)
The first cases of Emersonella pubipennis Hansson, 2002, Emersonella planiceps Hansson, 2002, Omphale huggerti (Hansson, 1988), Chrysocharis caribea Boucek, 1977, Chrysocharis vonones (Walker, 1839) and Chrysocharis tristis Hansson, 1987 (Hymenoptera, Eulophidae, Entedoninae) were reported for Coffea arabica L. based on specimens collected in Cravinhos (21°18’S/47°47’W), State of São Paulo, Brazil. The first occurrence of E. pubipennis and O. huggerti were also reported in Brazil. The insects were collected with Moericke and light traps between May of 2005 and April of 2007.